N, N′‐Bis(trifluoromethylsulfonyl)oxamidates: Synthesis and Thermal, Electrochemical, Spectroscopic, and Structural Properties1. Issue 34 (10th November 2015) - Sprenger, Jan A. P.; Konieczka, Szymon Z.; Brede, Franziska A.; Kerpen, Christoph; Drisch, Michael; Franz, Klaus‐Dieter; Ignat'ev, Nikolai; Reiss, Guido J.; Frank, Walter; Finze, Maik
Abstract: Salts of the N, N′ ‐bis(trifluoromethylsulfonyl)oxamidate dianion (1 2– ) were obtained by deprotonation of the oxamide CF3 SO2 NHC(O)2 (H2 1 ) with triethylamine, tri‐ n ‐octylamine, 1‐methylimidazole (MIM), and lithium hydride in yields of 61–92 %. The synthesis of H2 1 starting from oxalyl chloride and Na(NHSO2 CF3 ) was improved. The salts Li2 1, [Et3 NH]2 1, [ n Oct3 NH]2 1, and [HMIM]2 1 were characterized by multinuclear NMR, IR, and Raman spectroscopy, mass spectrometry, and thermal and elemental analysis. The electrochemical stability of dianion1 2– was studied by cyclic voltammetry on solutions of its lithium salt. The electrochemical properties are compared to those of H2 1 . The conductivity of Li2 1 in DME was found to be lower than those of Li[BF4 ] and LiCF3 SO3 . The structures of 1 ∞ [Li2 1· 2THF], [Et3 NH]2 1, [ n Oct3 NH]2 1, and [HMIM]2 1 were studied by single‐crystal X‐ray diffraction. In the solid state, dianion1 2– acts as a chelating ligand toward Li + and forms bifurcated hydrogen bonds with the N–H moieties of the organic cations. The discussion of selected spectroscopic and structural properties is aided by DFT calculations. Abstract : Salts of the N, N′ ‐bis(trifluoromethylsulfonyl)oxamidate dianion (1 2– ) were obtained by deprotonating CF3 SO2 NHC(O)2 with R3 N (R = Et, n Oct), 1‐methylimidazole (MIM), and LiH. The1 2– dianion acts as a chelating ligand toward Li + in the solid state and forms hydrogen bonds with the organic cations [R3 NH] + and [HMIM] + .